Implementasi Pasal 5 Perda No. 6 Tahun 2019 Tentang Penyelenggaraan Administrasi Kependudukan Di Kota Gorontalo - Albert Pede; Marwan Djafar; Yudin Yunus; Fahmi Kamuli (Unisan Law Review, 2025)
This research aims to (1) describe the implementation of Article 5 of Local Regulation No. 6 of 2019 concerning population administration in Gorontalo Municipality and (2) identify the factors affecting it. The type of legal research used is empirical legal research with a qualitative approach. Data collection is through interviews with employees of the Population and Civil Registration Office of Gorontalo Municipality and the community. This research shows that the implementation of Article 5 of Local Regulation No. 6 of 2019 concerning Population Administration in Gorontalo Municipality has not been fully optimal. Although regulations establish residents' rights to obtain population documents justly, equal services, and personal data protection, the facts indicate unequal services and indirect discrimination persist. The main factors affecting its implementation include a lack of professionalism and human resources at the Population and Civil Registration Office, as well as low public awareness of the importance of population administration. Therefore, it requires human resources and oversight to truly ensure the achievement of the objectives of the Local Regulation